FUNGSI KEARIFAN LOKAL DALAM MENANGGULANGI FUNDAMETALISME BERAGAMA DI MADURA - Encung, Encung (Universitas Al-Amien Prenduan, 2023)
AbstractThis research examines the role of local wisdom in strengthening the ethnic attitudes of the Madurese people which is used as one of the efforts to overcome religious fundamentalism. By using descriptive qualitative methods, this study answers two formulations of the problem, namely how the tanean rokat is implemented and what are the religious and cultural elements and how the tanean rokat has a role in forming a strong ethnic attitude that is able to dispel fundamentalism in religion so that it is concluded that the tanean rokat with the symbols contained in it and accompanied by the role of the figure